Neurocognitive evaluation in older adult patients affected by glioma. Issue 4 (May 2020) - Tanzilli, Antonio; Pace, Andrea; Fabi, Alessandra; Telera, Stefano; Vidiri, Antonello; Carosi, Mariantonia; Terrenato, Irene; Koudriavtseva, Tatiana; Boccaletti, Riccardo; Villani, Veronica
Abstract: Background: Glioblastoma (GBM) has an increasing incidence and dismal prognosis in older adults. This study evaluated neurocognitive status of an older adult population with GBM and its correlation with clinical and demographical variables. Methods: Each patient underwent an extended neuropsychological evaluation by means of a battery of standardized tests describing eight cognitive domains: global function; verbal learning; short- and long-term memory (LTM); executive functions (EFs); abstract reasoning (AR); attention; and visuo-constructional abilities (CA). Results: We assessed 79 patients with GBM (median age: 74 years). Out of this initial sample, a subgroup of seventeen patients with six-month median time underwent a follow-up test session. 46 out of the 79 patients (58.2%) presented multi-domain cognitive impairment, 24 patients (30.3%) showed single-domain cognitive impairment and only seven (9%) showed no cognitive impairment. Kaplan Meier estimator showed that patients with AR deficit had a poorer prognosis in terms of progression-free survival and overall survival ( p  < .001). At the multivariate analysis AR (deficit vs non; hazard ratio (HR) = 5.07, 95%; confidence interval (CI): 1.91–13.46; p  < .001) was correlated with disease progression and overall survival, AR (deficit vs non; HR = 7.24, 95% CI: 2.58–20.32; p < .001). Eight out of seventeen patients who underwent follow-up test session showed cognitive improvement, five resulted in further deterioration, and four patients remained stable. LTM, EF, and CA were the most affected functions at follow-up, while verbal learning was the most improved one in patients with cognitive improvement. Conclusions: Cognitive functioning evaluation should be included among the standard clinical endpoints in the treatment of older adult neuro-oncology patients.